Understanding the Shifts of Microbial Community and Metabolite Profile From Wheat to Mature Daqu - Zhang, Yuandi; Shen, Yi; Cheng, Wei; Wang, Xi; Xue, Yansong; Chen, Xiaoxue; Han, Bei-Zhong (Frontiers in Microbiology, 2021)
Wheat-originated microbes play an important role in shaping the quality of high-temperature Daqu which is commonly used as a starter for producing sauce-flavor Baijiu. However, the shifts of microbiota from raw material to fresh Daqu and then to mature Daqu remain unclear. Hence, in the present study, the inner and outer of fresh and mature Daqu were collected to explore the correlation between microbiota and metabolites as well as the source of the microbiota in Daqu. Results indicated that the activities of amylase and protease between the inner and outer of fresh Daqu varied significantly while both parts became similar after maturation. The predominant bacteria shifted from Saccharopolyspora (outer) and Staphylococcus (inner) to Kroppenstedtia (both outer and inner), while the predominant fungi shifted from Thermoascus (both outer and inner) to Byssochlamys (outer) and Fusarium (inner). A combining analysis of headspace solid-phase micro extraction-gas chromatography-mass spectrometry, headspace gas chromatography-ion mobility spectrometry, and nuclear magnetic resonance was employed to detect the metabolites. The network analysis was conducted to perform the relationships between microbes and metabolites. The results showed that the bacteria, especially Saccharopolyspora, Bacillus, and Acinetobacter, had a strong correlation with the productions of esters, amino acids and their derivatives, and sugars and their derivatives, while most fungi such as Thermoascus, were negatively correlated with the phenylalanine, trimethylamine n-oxide, and isovalerate. SourceTracker analysis indicated that wheat was the important source of the Daqu microbiota, especially, the microorganisms in the inner of Daqu might be the drivers of the microbial succession during maturation. This study provided a comprehensive exploration to understand the microbial sources and shifts in high-temperature Daqu during maturation.